Assessing perioperative complications associated with use of intraoperative magnetic resonance imaging during glioma surgery: a single centre experience with 516 cases - Ahmadi, Rezvan; Campos, Benito; Haux-Nettesheim, Daniel; Rieke, Jörn; Beigel, Bernhard; Unterberg, Andreas (British journal of neurosurgery, 2016)
Background: Intraoperative magnetic resonance imaging (io-MRI) improves the extent of glioma resection. Due to the magnetic field, patients have to be covered with sterile drape and are then transferred into an io-MRI chamber, where ferromagnetic anaesthesia monitors and machines must be kept at distance and can only be applied with limitations. Despite the development of specific paramagnetic equipment for io-MRI use, this method is suspected to carry a higher risk for anaesthesiological and surgical complications. Particularly, serial draping and un-draping cycles as well as the extended surgery duration might increase the risk of perioperative infection. Objective: Given the importance of io-MRI for glioma surgery, the question regarding io-MRI safety needs to be answered. Methods: We prospectively evaluate the perioperative anaesthesiological and surgical complications for 516 cases of brain tumour surgery involving io-MRI (MRI cohort). As a control group, we evaluate a cohort of 610 cases of brain tumour surgery, performed without io-MRI (control group). Results: The io-MRI procedure (including draping/undraping, transfer to and from the MRI cabinet and io-MRI scan) significantly extended surgery, defined as “skin to skin” time, by 57 min (SD = 16 min) (p ≤ 0.01). Still, we show low and comparable rates of surgical complications in the MRI cohort and the control group. Postoperative haemorrhage (3.7% versus 3.0% in MRI cohort versus control group; p = 0.49) and infections (2.2% versus 1.8% in MRI cohort versus control group; p = 0.69) were not significantly different between both groups. No anaesthesiological disturbances were reported. Conclusion: Despite prolonged surgery and serial draping and un-draping cycles, io-MRI was not linked to higher rates of infections and postoperative haemorrhage in this study.
Gesehen am 12.08.2020